Sealant for organic EL display elements
By using sealants of cycloolefin oxide alicyclic epoxy compounds and biphenyl skeleton compounds in organic EL display elements, combined with thermal cationic polymerization initiator, the problems of poor degassing properties and low light extraction efficiency are solved, and the sealant is achieved. Efficient light extraction and stable sealing effect.
Patent Information
- Application Number
- CN202080015920.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-17
- Filing Date
- 2020-07-07
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-07-07
AI Technical Summary
The existing organic EL display element sealants have problems such as poor degassing properties and low light extraction efficiency, especially in top-emitting organic EL display elements, which leads to light extraction efficiency due to the difference in refractive index between the electrode or passivation film and the sealant. reduce.
A sealant containing a cycloolefin oxide alicyclic epoxy compound and a cationic polymerizable compound having a biphenyl backbone and an epoxy or oxetane group, and a thermal cationic polymerization initiator is used to achieve low temperature curing. Optimize the composition of the sealant to improve low degassing and coating properties.
The organic EL display element has been achieved with excellent low degassing properties and coating properties, significantly improving the light extraction efficiency, and stable curing of the sealant is achieved below 100°C.
Smart Images

Figure BDA0003222223350000041 
Figure BDA0003222223350000211 
Figure BDA0003222223350000221
Abstract
Description
Technical Field
[0001] The present invention relates to a sealing agent for an organic EL display element, which has low outgassing properties and excellent coating properties and can provide an organic EL display element excellent in light extraction efficiency. Background Art
[0002] An organic electroluminescent (hereinafter also referred to as "organic EL") display element has a laminated structure in which an organic light-emitting material layer is sandwiched between a pair of electrodes facing each other. Electrons are injected into the organic light-emitting material layer from one electrode, and holes are injected into the organic light-emitting material layer from the other electrode, so that the electrons and holes are combined in the organic light-emitting material layer to emit light. As such, an organic EL display element emits light by itself, and therefore has the advantages of good visual recognition, further thinning, and DC low-voltage drive compared to liquid crystal display elements that require backlights.
[0003] The organic light-emitting material layer or electrode constituting the organic EL display element has the problem that the characteristics are easily degraded due to moisture, oxygen, etc. Therefore, in order to obtain a practical organic EL display element, it is necessary to isolate the organic light-emitting material layer or electrode from the atmosphere to achieve a long life. As a method of isolating the organic light-emitting material layer or electrode from the atmosphere, a sealant is used to seal the organic EL display element (for example, Patent Document 1). When the organic EL display element is sealed with a sealant, in order to fully suppress the penetration of moisture, oxygen, etc., an inorganic material film called a passivation film is usually provided on a laminate having an organic light-emitting material layer, and the inorganic material film is sealed with a sealant.
[0004] In recent years, top-emitting organic EL display elements that extract light from the upper side of the organic light-emitting layer have attracted attention, replacing the bottom-emitting organic EL display elements that extract light emitted from the organic light-emitting material layer on the substrate surface side where the light-emitting element is formed. This method has a high aperture ratio and low voltage drive, so it has the advantage of long life. In such a top-emitting organic EL display element, since the upper side of the light-emitting layer must be transparent, a transparent moisture-proof substrate such as glass is laminated on the upper side of the light-emitting element via a transparent sealing layer to perform sealing (for example, Patent Document 2). However, in the top-emitting organic EL display element, even if a material with sufficiently high transparency is used as a transparent moisture-proof substrate or sealant, there will be a problem of poor extraction efficiency of light emitted from the laminate due to the difference in refractive index between the electrode or passivation film and the sealant. In addition, the existing sealant has the problem of degassing and deterioration of the element, and poor coating performance. In addition, in order to reduce the damage to the organic EL display element due to heating, the sealant also needs to be curable at low temperature.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2007-115692
[0008] Patent Document 2: Japanese Patent Application Publication No. 2009-051980 Summary of the invention
[0009] Problems to be solved by the invention
[0010] An object of the present invention is to provide a sealing agent for an organic EL display element which has excellent low degassing property and coating property and can obtain an organic EL display element excellent in light extraction efficiency.
[0011] Means for solving problems
[0012] The sealing agent for an organic EL display element of the present invention contains a cationically polymerizable compound and a cationic polymerization initiator, wherein the cationically polymerizable compound contains a cycloolefin oxide-type alicyclic epoxy compound and a compound having a biphenyl skeleton and an epoxy group or an oxetane group.
[0013] The present invention will be described in detail below.
[0014] The present inventors have studied the use of cycloolefin oxide type alicyclic epoxy compounds as cationic polymerizable compounds in sealants for organic EL display elements to improve coating properties and prevent the generation of degassing. However, even if the sealant using such cycloolefin oxide type alicyclic epoxy compounds is excellent in the effect of preventing the generation of degassing, the difference in refractive index with the electrode or passivation film is large, so there is a problem of reduced light extraction efficiency due to reflection at the interface between the electrode or passivation film and the sealant. Therefore, the present inventors studied the use of the cycloolefin oxide type alicyclic epoxy compound in combination with a compound having a biphenyl skeleton and an epoxy group or an oxetane group as a cationic polymerizable compound. As a result, it was found that a sealant for an organic EL display element having low degassing properties and excellent coating properties, and excellent light extraction efficiency of the obtained organic EL display element can be obtained, thereby completing the present invention.
[0015] When a thermal cationic polymerization initiator is used as the cationic polymerization initiator and the sealing agent for an organic EL display element of the present invention is a thermosetting sealing agent, it can be easily cured at a low temperature of 100° C. or lower.
[0016] The sealing agent for an organic EL display element of the present invention contains a cationically polymerizable compound.
[0017] The cationically polymerizable compound includes a cycloolefin oxide type alicyclic epoxy compound. By including the cycloolefin oxide type alicyclic epoxy compound, the sealing agent for an organic EL display element of the present invention has excellent low outgassing property and coating property.
[0018] Examples of the cycloolefin oxide type alicyclic epoxy compounds include 3′,4′-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, bis(3,4-epoxycyclohexylmethyl) ether, bis(3,4-epoxycyclohexane-1-ylmethyl) adipate, 1,2-epoxy-4-(2-epoxyethyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol, and [(3,4-epoxycyclohexane)-1-yl]methyl methacrylate.
[0019] As what is commercially available among the said cycloolefin oxide type alicyclic epoxy compounds, Celloxide 2021P (made by Daicel), TTA26 (made by Sun Chemical Co., Ltd.), EHPE3150 (made by Daicel Co., Ltd.), etc. are mentioned.
[0020] In 100 parts by weight of the above-mentioned cationic polymerizable compound as a whole, the content of the above-mentioned cycloolefin oxide type alicyclic epoxy compound is preferably limited to 3 parts by weight, and the preferred upper limit is 45 parts by weight. When the content of the above-mentioned cycloolefin oxide type alicyclic epoxy compound is 3 parts by weight or more, the curability, low degassing and coating properties of the obtained sealant for the organic EL display element are more excellent. When the content of the above-mentioned cycloolefin oxide type alicyclic epoxy compound is 45 parts by weight or less, the light extraction efficiency of the obtained organic EL display element is more excellent. The content of the above-mentioned cycloolefin oxide type alicyclic epoxy compound is more preferably limited to 5 parts by weight, more preferably limited to 40 parts by weight, and further preferably limited to 38 parts by weight.
[0021] The cationic polymerizable compound includes a compound having a biphenyl skeleton and an epoxy group or an oxetane group. By containing the compound having a biphenyl skeleton and an epoxy group or an oxetane group, the difference in refractive index between the sealant for the organic EL display element of the present invention and the electrode or the passivation film is small, and as a result, the light extraction efficiency of the obtained organic EL display element is excellent. In addition, by containing a compound having a biphenyl skeleton and an epoxy group or an oxetane group, when the sealant for the organic EL display element of the present invention is used as a thermosetting sealant, it can be easily cured at a low temperature below 100°C.
[0022] The compound having a biphenyl skeleton and an epoxy group or an oxetane group may be an epoxy compound having a biphenyl skeleton or an oxetane compound having a biphenyl skeleton, and compounds having various biphenyl skeletons and epoxy groups or oxetane groups may be appropriately selected from the viewpoints of viscosity, refractive index, photocurability, etc.
[0023] Specific examples of the compound having a biphenyl skeleton and an epoxy group or an oxetane group include o-phenylphenol glycidyl ether, a compound represented by the following formula (1), p-phenylphenol glycidyl ether, 4,4-biphenyldiyl bis(glycidyl ether), 4,4′-bis(glycidyloxy)-1,1′-biphenyl, and 3,3′,5,5′-tetramethyl-4,4′-bis(glycidyloxy)-1,1′-biphenyl. Among them, o-phenylphenol glycidyl ether and a compound represented by the following formula (1) are preferred.
[0024] The above-mentioned compounds having a biphenyl skeleton and an epoxy group or an oxetane group may be used alone or in combination of two or more.
[0025] [Chemical formula 1]
[0026]
[0027] In formula (1), n is the number of repetitions.
[0028] This n is preferably a value such that the compound represented by the formula (1) satisfies the following range of oxetane equivalent.
[0029] The preferred lower limit of the epoxy equivalent or oxetane equivalent of the compound having a biphenyl skeleton and an epoxy group or an oxetane group is 110, and the preferred upper limit is 500. When the epoxy equivalent or oxetane equivalent of the compound having a biphenyl skeleton and an epoxy group or an oxetane group is within this range, the obtained sealant for an organic EL display element has better adhesion, low degassing properties, and coating properties.
[0030] Moreover, in the present specification, the epoxy equivalent or oxetane equivalent of the above-mentioned compound having a biphenyl skeleton and an epoxy group or an oxetane group means: (molecular weight of the compound having a biphenyl skeleton and an epoxy group or an oxetane group) / (the number of epoxy groups or oxetane groups in one molecule of the compound having a biphenyl skeleton and an epoxy group or an oxetane group).
[0031] The preferred lower limit of the molecular weight of the compound having a biphenyl skeleton and an epoxy group or an oxetane group is 200, and the preferred upper limit is 1000. When the molecular weight of the compound having a biphenyl skeleton and an epoxy group or an oxetane group is within this range, the obtained sealant for an organic EL display element has better adhesion, low degassing properties, and coating properties.
[0032] And in this manual, about above-mentioned " molecular weight ", for the compound with definite molecular structure, it is the molecular weight sought by structural formula, but for the compound with wider distribution of polymerization degree and the compound with uncertain modification part, molecular weight is sometimes represented by weight average molecular weight.In addition, above-mentioned " weight average molecular weight " is to use tetrahydrofuran as solvent, uses gel permeation chromatography (GPC) to measure, and converts and seeks the value with polystyrene.As the column used when measuring the weight average molecular weight converted with polystyrene by GPC, for example Shodex LF-804 (Showa Denko Co., Ltd. system) etc. can be listed.
[0033] The compound having a biphenyl skeleton and an epoxy group or an oxetane group is preferably liquid at 25° C. When the epoxy equivalent or oxetane equivalent of the compound having a biphenyl skeleton and an epoxy group or an oxetane group is liquid at 25° C., the coating property of the obtained sealing agent for an organic EL display element is further improved.
[0034] Examples of commercially available compounds having a biphenyl skeleton and an epoxy group or an oxetane group include OPP-EP (manufactured by Yokkaichi Kosei Co., Ltd.) and ETERNACOLL OXBP (manufactured by Ube Industries, Ltd.).
[0035] In the above-mentioned cationic polymerizable compound as a whole 100 parts by weight, the preferred lower limit of the content of the compound having a biphenyl skeleton and an epoxy group or an oxetane group is 30 parts by weight, and the preferred upper limit is 97 parts by weight. When the content of the compound having a biphenyl skeleton and an epoxy group or an oxetane group is 30 parts by weight or more, the light extraction efficiency of the obtained organic EL display element is more excellent. When the content of the compound having a biphenyl skeleton and an epoxy group or an oxetane group is less than 97 parts by weight, the curability, low degassing and coating properties of the obtained organic EL display element sealant are more excellent. The more preferred lower limit of the content of the compound having a biphenyl skeleton and an epoxy group or an oxetane group is 50 parts by weight, the more preferred upper limit is 90 parts by weight, and the further preferred upper limit is 80 parts by weight.
[0036] When the content of the cycloolefin oxide type alicyclic epoxy compound is set to 1, the content ratio of the compound having a biphenyl skeleton and an epoxy group or an oxetane group is calculated by weight ratio, preferably with a lower limit of 1 and an upper limit of 20. When the content ratio of the compound having a biphenyl skeleton and an epoxy group or an oxetane group is 1 or more, the refractive index (light extraction efficiency) of the obtained sealant for an organic EL display element is more excellent, and when the content ratio is 20 or less, the curability and refractive index are more excellent. The content ratio of the compound having a biphenyl skeleton and an epoxy group or an oxetane group is more preferably 1.3, more preferably 15, further preferably 1.4, and further preferably 10.
[0037] The cationically polymerizable compound includes the cycloolefin oxide-type alicyclic epoxy compound and the compound having a biphenyl skeleton and an epoxy group or an oxetane group, and may include other cationically polymerizable compounds.
[0038] Examples of the other cationically polymerizable compounds include other epoxy compounds other than the cycloolefin oxide-type alicyclic epoxy compounds and the compounds having a biphenyl skeleton and an epoxy group or an oxetane group, other oxetane compounds, and vinyl ether compounds.
[0039] Examples of the other epoxy compounds include fluorene-type epoxy compounds, 1,7-octadiene diepoxy compounds, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerol diglycidyl ether, trimethylolpropane triglycidyl ether, phenyl glycidyl ether, and phenylene diglycidyl ether.
[0040] Examples of the other oxetane compounds include 3-ethyl-3-(((3-ethyloxetan-3-yl)methoxy)methyl)oxetane, 3-ethyl-3-((2-ethylhexyloxy)methyl)oxetane, 3-ethyl-3-(((3-(triethoxysilyl)propoxy)methyl)oxetane, novolac oxetane, and 1,4-bis(((3-ethyl-3-oxetanyl)methoxy)methyl)benzene.
[0041] Examples of the vinyl ether compound include benzyl vinyl ether, cyclohexanedimethanol monovinyl ether, dicyclopentadiene vinyl ether, 1,4-butanediol divinyl ether, cyclohexanedimethanol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, dipropylene glycol divinyl ether, and tripropylene glycol divinyl ether.
[0042] Among them, as the above-mentioned other cationically polymerizable compound, at least one of 3-ethyl-3-(((3-ethyloxetane-3-yl)methoxy)methyl)oxetane, 1,2:7,8-diepoxyoctane, and 1,2:5,6-diepoxycyclooctane is preferred, and 3-ethyl-3-(((3-ethyloxetane-3-yl)methoxy)methyl)oxetane is more preferred.
[0043] When the above-mentioned cationic polymerizable compound contains the above-mentioned other cationic polymerizable compound, the preferred lower limit of the content of the above-mentioned other cationic polymerizable compound in 100 parts by weight of the above-mentioned cationic polymerizable compound is 1 part by weight, and the preferred upper limit is 60 parts by weight. When the content of the above-mentioned other cationic polymerizable compound is within this range, the adhesion and coating properties of the obtained sealant for organic EL display elements are more excellent. The more preferred lower limit of the content of the above-mentioned other cationic polymerizable compound is 10 parts by weight, the more preferred upper limit is 50 parts by weight, the further preferred lower limit is 15 parts by weight, and the further preferred upper limit is 40 parts by weight.
[0044] In addition, when the above-mentioned cationic polymerizable compound includes the above-mentioned other cationic polymerizable compound, the total content of the above-mentioned cycloolefin oxide type alicyclic epoxy compound and the above-mentioned other cationic polymerizable compound in 100 parts by weight of the above-mentioned cationic polymerizable compound is preferably limited to 20 parts by weight. When the total content of the above-mentioned cycloolefin oxide type alicyclic epoxy compound and the above-mentioned other cationic polymerizable compound is 20 parts by weight or more, the coating property of the obtained sealant for organic EL display elements is more excellent. The total content of the above-mentioned cycloolefin oxide type alicyclic epoxy compound and the above-mentioned other cationic polymerizable compound is more preferably limited to 25 parts by weight.
[0045] The sealing agent for an organic EL display element of the present invention contains a cationic polymerization initiator.
[0046] Examples of the cationic polymerization initiator include thermal cationic polymerization initiators and photocationic polymerization initiators. In particular, when a thermal cationic polymerization initiator is used as the cationic polymerization initiator, the sealant for an organic EL display element of the present invention can be easily cured at a low temperature of 100° C. or lower.
[0047] As the thermal cationic polymerization initiator, the anion part is composed of BF 4 - PF 6 - , SbF 6 - or (BX 4 ) -(wherein X represents a phenyl group substituted with at least two or more fluorine or trifluoromethyl groups) sulfonium salts, phosphonium salts, ammonium salts, diazonium salts, iodonium salts, etc. Among them, sulfonium salts are preferred.
[0048] Examples of the sulfonium salt include triphenylsulfonium tetrafluoroborate and triphenylsulfonium hexafluoroantimonate.
[0049] Examples of the phosphonium salt include ethyltriphenylphosphonium hexafluoroantimonate and tetrabutylphosphonium hexafluoroantimonate.
[0050] Examples of the ammonium salt include dimethylphenyl(4-methoxybenzyl)ammonium hexafluorophosphate, dimethylphenyl(4-methoxybenzyl)ammonium hexafluoroantimonate, dimethylphenyl(4-methoxybenzyl)ammonium tetrakis(pentafluorophenyl)borate, dimethylphenyl(4-methylbenzyl)ammonium hexafluorophosphate, dimethylphenyl(4-methylbenzyl)ammonium hexafluoroantimonate, dimethylphenyl(4-methylbenzyl)ammonium hexafluorotetrakis(pentafluorophenyl)borate, methylphenyldibenzylammonium hexafluorophosphate, Methylphenyldibenzylammonium hexafluoroantimonate, methylphenyldibenzylammonium tetra(pentafluorophenyl)borate, phenyltribenzylammonium tetra(pentafluorophenyl)borate, dimethylphenyl(3,4-dimethylbenzyl)ammonium tetra(pentafluorophenyl)borate, N,N-dimethyl-N-benzylanimmonium hexafluoroantimonate, N,N-diethyl-N-benzylanimmonium tetrafluoroborate, N,N-dimethyl-N-benzylpyridinium hexafluoroantimonate, N,N-diethyl-N-benzylpyridinium trifluoromethanesulfonic acid, etc.
[0051] Examples of commercially available thermal cationic polymerization initiators include thermal cationic polymerization initiators manufactured by Sanshin Chemical Industry Co., Ltd. and thermal cationic polymerization initiators manufactured by King Industries, Ltd.
[0052] Examples of the thermal cationic polymerization initiator manufactured by Sanshin Chemical Industry Co., Ltd. include San Aid SI-60, San Aid SI-80, San Aid SI-B3, San Aid SI-B3A, and San Aid SI-B4.
[0053] Examples of the thermal cationic polymerization initiator manufactured by King Industries include CXC-1612 and CXC-1821.
[0054] The photocationic polymerization initiator is not particularly limited as long as it generates a protonic acid or a Lewis acid by light irradiation, and may be an ionic photoacid generating type or a nonionic photoacid generating type.
[0055] Examples of the anion portion of the ionic photoacid generating type photocationic polymerization initiator include BF 4 - PF 6 - , SbF 6 - 、(BX 4 ) - (wherein X represents a phenyl group substituted with at least two or more fluorine or trifluoromethyl groups) etc. In addition, as the above-mentioned anion part, PF m (C n F 2n+1 ) 6-m - (wherein m is an integer from 0 to 5, and n is an integer from 1 to 6), etc.
[0056] Examples of the ionic photoacid generating photocationic polymerization initiator include aromatic sulfonium salts, aromatic iodonium salts, aromatic diazonium salts, aromatic ammonium salts, and (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe salts having the anion moiety.
[0057] Examples of the aromatic sulfonium salts include bis(4-(diphenylsulfonium)phenyl)sulfide bishexafluorophosphate, bis(4-(diphenylsulfonium)phenyl)sulfide bishexafluoroantimonate, bis(4-(diphenylsulfonium)phenyl)sulfide bistetrafluoroborate, bis(4-(diphenylsulfonium)phenyl)sulfide tetrakis(pentafluorophenyl)borate, diphenyl 4-(phenylthio)phenylsulfonium hexafluorophosphate, diphenyl-4-(phenylthio)phenylsulfonium hexafluoroantimonate, diphenyl-4-(phenylthio)phenylsulfonium tetrafluoroborate, diphenyl-4-(phenylthio)phenylsulfonium tetrakis(pentafluorophenyl)borate, triphenylsulfonium hexafluorophosphate, triphenylsulfonium Sulfonium hexafluoroantimonate, triphenylsulfonium tetrafluoroborate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide bishexafluorophosphate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide bishexafluoroantimonate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide bistetrafluoroborate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide tetrakis(pentafluorophenyl)borate, tris(4-(4-acetylphenyl)phenylthio)sulfide tetrakis(pentafluorophenyl)borate, etc. Among them, triarylsulfonium tetrakis(pentafluorophenyl)borate, such as triphenylsulfonium tetrakis(pentafluorophenyl)borate, is preferred.
[0058] Examples of the aromatic iodonium salt include diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, diphenyliodonium tetrafluoroborate, diphenyliodonium tetrakis(pentafluorophenyl)borate, bis(dodecylphenyl)iodonium hexafluorophosphate, bis(dodecylphenyl)iodonium hexafluoroantimonate, bis(dodecylphenyl)iodonium tetrafluoroborate, bis(dodecylphenyl)iodonium tetrakis(pentafluorophenyl)borate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluorophosphate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluoroantimonate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium tetrakis(pentafluorophenyl)borate, and the like.
[0059] Examples of the aromatic diazonium salt include phenyldiazonium hexafluorophosphate, phenyldiazonium hexafluoroantimonate, phenyldiazonium tetrafluoroborate, and phenyldiazonium tetrakis(pentafluorophenyl)borate.
[0060] Examples of the aromatic ammonium salt include 1-benzyl-2-cyanopyridinium hexafluorophosphate, 1-benzyl-2-cyanopyridinium hexafluoroantimonate, 1-benzyl-2-cyanopyridinium tetrafluoroborate, 1-benzyl-2-cyanopyridinium tetrakis(pentafluorophenyl)borate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluorophosphate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluoroantimonate, 1-(naphthylmethyl)-2-cyanopyridinium tetrakis(pentafluorophenyl)borate, and the like.
[0061] Examples of the above-mentioned (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe salt include (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluorophosphate, (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluoroantimonate, (2,4-cyclopentadien-1)-yl)((1-methylethyl)benzene)-Fe(II) tetrafluoroborate, and (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) tetrakis(pentafluorophenyl)borate.
[0062] Examples of the nonionic photoacid generating type photocationic polymerization initiator include nitrobenzyl esters, sulfonic acid derivatives, phosphoric acid esters, phenolsulfonic acid esters, naphthoquinone diazide, and N-hydroxyimidesulfonic acid esters.
[0063] Examples of commercially available photocationic polymerization initiators include photocationic polymerization initiators manufactured by Midori Chemical Co., Ltd., photocationic polymerization initiators manufactured by Union Carbide Co., Ltd., photocationic polymerization initiators manufactured by ADEKA Co., Ltd., photocationic polymerization initiators manufactured by 3M Co., Ltd., photocationic polymerization initiators manufactured by BASF Co., Ltd., photocationic polymerization initiators manufactured by Solvay Co., Ltd., and photocationic polymerization initiators manufactured by San-Apro Co., Ltd.
[0064] Examples of the photocationic polymerization initiator manufactured by Midori Chemical Co., Ltd. include DTS-200 and the like.
[0065] Examples of the photocationic polymerization initiator manufactured by the Union Carbide company include UVI6990 and UVI6974.
[0066] Examples of the photocationic polymerization initiator manufactured by ADEKA Corporation include SP-150 and SP-170.
[0067] Examples of the photocationic polymerization initiator manufactured by 3M include FC-508 and FC-512.
[0068] Examples of the photocationic polymerization initiator manufactured by BASF include IRGACURE 261 and IRGACURE 290.
[0069] Examples of the photocationic polymerization initiator manufactured by Solvay include PI2074.
[0070] Examples of the photocationic polymerization initiator manufactured by San-Apro include CPI-100P, CPI-200K, and CPI-210S.
[0071] Among the above-mentioned cationic polymerization initiators, it is preferable to use a quaternary ammonium salt whose counter anion is a borate-based salt (hereinafter also referred to as a “borate-based quaternary ammonium salt”).
[0072] The counter anion of the borate quaternary ammonium salt is preferably BF 4 - or (BX 4 ) - (wherein X represents a phenyl group substituted with at least two or more fluorine or trifluoromethyl groups).
[0073] The content of the above-mentioned cationic polymerization initiator is preferably 0.05 parts by weight relative to 100 parts by weight of the above-mentioned cationic polymerizable compound, and the preferred upper limit is 10 parts by weight. When the content of the above-mentioned cationic polymerization initiator is within this range, the curability, storage stability and moisture resistance of the cured product of the obtained organic EL display element sealant are more excellent. The more preferred lower limit of the content of the above-mentioned cationic polymerization initiator is 0.1 parts by weight, and the more preferred upper limit is 5 parts by weight.
[0074] The sealing agent for an organic EL display element of the present invention may contain a thermosetting agent.
[0075] Examples of the thermosetting agent include hydrazide compounds, imidazole derivatives, acid anhydrides, dicyandiamide, guanidine derivatives, modified aliphatic polyamines, and addition products of various amines and epoxy resins.
[0076] Examples of the hydrazide compound include 1,3-bis(hydrazinocarbonylethyl)-5-isopropylhydantoin, sebacic acid dihydrazide, isophthalic acid dihydrazide, adipic acid dihydrazide, and malonic acid dihydrazide.
[0077] Examples of the imidazole derivatives include 1-cyanoethyl-2-phenylimidazole, N-(2-(2-methyl-1-imidazolyl)ethyl)urea, 2,4-diamino-6-(2′-methylimidazolyl-(1′))-ethyl-s-triazine, N,N′-bis(2-methyl-1-imidazolylethyl)urea, N,N′-(2-methyl-1-imidazolylethyl)-adipic acid diamide, 2-phenyl-4-methyl-5-hydroxymethylimidazole, and 2-phenyl-4,5-dihydroxymethylimidazole.
[0078] Examples of the acid anhydride include tetrahydrophthalic anhydride and ethylene glycol bis(anhydrotrimellitate).
[0079] These thermosetting agents may be used alone or in combination of two or more.
[0080] Examples of commercially available thermosetting agents include thermosetting agents manufactured by Otsuka Chemical Co., Ltd. and thermosetting agents manufactured by Ajinomoto Dine-Techno Co., Ltd.
[0081] Examples of the thermosetting agent manufactured by Otsuka Chemical Co., Ltd. include SDH and ADH.
[0082] Examples of the thermosetting agent manufactured by Ajinomoto Dine-Techno include Ajicure VDH, Ajicure VDH-J, and Ajicure UDH.
[0083] Relative to 100 parts by weight of the cationic polymerizable compound, the content of the thermosetting agent is preferably limited to 0.5 parts by weight, and preferably limited to 30 parts by weight. When the content of the thermosetting agent is 0.5 parts by weight or more, the thermosetting property of the obtained organic EL display element sealant is more excellent. When the content of the thermosetting agent is 30 parts by weight or less, the storage stability of the obtained organic EL display element sealant is more excellent, and the moisture resistance of the cured product is more excellent. The more preferred lower limit of the content of the thermosetting agent is 1 part by weight, and the more preferred upper limit is 15 parts by weight.
[0084] The sealing agent for an organic EL display element of the present invention preferably contains a stabilizer. By containing the stabilizer, the sealing agent for an organic EL display element of the present invention has further excellent storage stability.
[0085] As the stabilizer, an aromatic amine compound is preferably used.
[0086] Examples of the aromatic amine compound include benzylamine and aminophenol-type epoxy resins.
[0087] Examples of the aminophenol-type epoxy resin include triglycidyl-p-aminophenol and the like.
[0088] Among them, benzylamine is preferred.
[0089] These stabilizers may be used alone or in combination of two or more.
[0090] The content of the stabilizer is preferably 0.001 parts by weight relative to 100 parts by weight of the cationic polymerizable compound, and preferably 2 parts by weight. When the content of the stabilizer is within this range, the obtained sealant for organic EL display elements has excellent curability while maintaining excellent storage stability. The more preferred lower limit of the content of the stabilizer is 0.005 parts by weight, and the more preferred upper limit is 1 part by weight.
[0091] The sealing agent for an organic EL display element of the present invention may contain a silane coupling agent. The silane coupling agent has a function of improving the adhesion between the sealing agent for an organic EL display element of the present invention and a substrate or the like.
[0092] Examples of the silane coupling agent include 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-isocyanatepropyltrimethoxysilane, etc. These silane coupling agents may be used alone or in combination of two or more.
[0093] The content of the silane coupling agent is preferably limited to 0.1 parts by weight and preferably limited to 10 parts by weight relative to 100 parts by weight of the cationic polymerizable compound. When the content of the silane coupling agent is within this range, the effect of improving adhesion becomes more excellent while suppressing the excessive silane coupling agent from seeping out. The more preferred lower limit of the content of the silane coupling agent is 0.5 parts by weight and the more preferred upper limit is 5 parts by weight.
[0094] From the viewpoint of low degassing properties, the upper limit of the content of the silane coupling agent is preferably 0.5 parts by weight, more preferably 0.1 parts by weight, and still more preferably 0.01 parts by weight based on 100 parts by weight of the cationically polymerizable compound.
[0095] The sealing agent for an organic EL display element of the present invention may contain a surface modifier unless the object of the present invention is impaired. By containing the surface modifier, the flatness of the coating film of the sealing agent for an organic EL display element of the present invention can be improved.
[0096] Examples of the surface modifier include surfactants and leveling agents.
[0097] Examples of the surface modifier include silicone-based, acrylic-based, and fluorine-based agents.
[0098] Examples of commercially available surface modifiers include surface modifiers manufactured by BYK-Chemie (Japan) Co., Ltd. and surface modifiers manufactured by AGC Seimi Chemical Co., Ltd.
[0099] Examples of the surface modifier manufactured by BYK-Chemie (Japan) include BYK-330, BYK-340, and BYK-345.
[0100] Examples of the surface modifier manufactured by AGC Seimi Chemical Co., Ltd. include Surflon S-611.
[0101] The sealing agent for an organic EL display element of the present invention may contain a compound or an ion exchange resin that reacts with an acid generated in the sealing agent for an organic EL display element in order to improve the durability of the element electrode, within a range not impairing the object of the present invention.
[0102] Examples of the compound that reacts with the generated acid include substances that neutralize the acid, such as alkali metal carbonates or hydrogen carbonates, or alkaline earth metal carbonates or hydrogen carbonates, etc. Specifically, for example, calcium carbonate, calcium hydrogen carbonate, sodium carbonate, sodium hydrogen carbonate, etc. are used.
[0103] As the ion exchange resin, any of a cation exchange type, anion exchange type, and a dual ion exchange type can be used, and a cation exchange type or a dual ion exchange type capable of adsorbing chloride ions is particularly preferred.
[0104] The sealant for the organic EL display element of the present invention may contain a solvent for the purpose of viscosity adjustment, but there are problems such as degradation of the organic light-emitting material layer due to residual solvent and degassing, so it is preferably free of solvent or the solvent content is 0.05 wt % or less.
[0105] Furthermore, the sealing agent for an organic EL display element of the present invention may contain various known additives such as a curing retardant, a reinforcing agent, a softener, a plasticizer, a viscosity modifier, an ultraviolet absorber, and an antioxidant, as required.
[0106] The upper limit of the viscosity of the sealant for organic EL display elements of the present invention measured by using an E-type viscometer at 25° C. and 2.5 rpm is preferably 2000 mPa·s. When the above viscosity is 2000 mPa·s or less, the coating property of the sealant for organic EL display elements obtained is excellent. The upper limit of the above viscosity is more preferably 1500 mPa·s, and the upper limit is further preferably 1000 mPa·s.
[0107] Furthermore, a preferred lower limit of the viscosity is 10 mPa·s.
[0108] The viscosity can be measured on a CP1 cone plate using, for example, VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) as an E-type viscometer.
[0109] The sealant for an organic EL display element of the present invention has a preferably lower limit of a refractive index of a sodium D line at 25° C. of a cured product of 1.55. When the refractive index is within this range, the difference in refractive index with the electrode or the passivation film becomes small, and as a result, the light extraction efficiency of the obtained organic EL display element becomes excellent. A more preferred lower limit of the refractive index is 1.56.
[0110] The above-mentioned “refractive index of sodium D line” can be measured using an Abbe refractometer.
[0111] In addition, as the above-mentioned cured product for measuring the refractive index, a measuring piece with a length of 20 mm, a width of 10 mm, and a thickness of about 0.5 mm to 1 mm is used. If the above-mentioned cured product for measuring the refractive index is a thermosetting sealant, it can be obtained by heating at 100°C for 30 minutes, and if it is a photothermosetting sealant, it can be obtained by heating at 2000mJ / cm 2 It can be obtained by irradiating with ultraviolet rays of about 100°C and then heating at 100°C for 30 minutes.
[0112] The sealing agent for an organic EL display element of the present invention is particularly preferably used as an in-plane sealing agent for coating and sealing a laminated body having an organic light-emitting material layer.
[0113] Furthermore, the sealing agent for an organic EL display element of the present invention is preferably used for sealing a top emission type organic EL display element.
[0114] As a method for sealing an organic EL display element using the sealant for an organic EL display element of the present invention, for example, a method having the following steps: a step of applying the sealant for an organic EL display element of the present invention to a substrate by printing, dispensing or inkjet method on the surface of the organic EL display element substrate, and a method of curing the applied sealant for an organic EL display element by heating and / or light irradiation, etc.
[0115] In the process of coating the sealant for the organic EL display element of the present invention on the substrate, the sealant for the organic EL display element of the present invention may be coated on the entire substrate or on a portion of the substrate. The shape of the sealing portion of the sealant for the organic EL display element of the present invention formed by coating is not particularly limited as long as it is a shape that can protect the laminate having the organic light-emitting material layer from the influence of external gas, and may be a shape that completely covers the laminate, may be a closed pattern formed at the peripheral edge of the laminate, or may be a pattern with a shape having a partial opening formed at the peripheral edge of the laminate.
[0116] When the organic EL display element sealant is cured by heating, it is preferably heated at 50° C. or higher and 120° C. or lower from the viewpoint of sufficiently curing the laminate having the organic light-emitting material layer while reducing damage thereto.
[0117] When the sealing agent for an organic EL display element of the present invention is cured by irradiating light with a wavelength of 300 nm to 400 nm and 300 mJ / cm 2 Above and 3000mJ / cm 2 The light having the following integrated light amount can appropriately cure.
[0118] As the light source used in the above-mentioned light irradiation, for example, low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, excimer lasers, chemical lamps, black light lamps, microwave-excited mercury lamps, metal halide lamps, sodium lamps, halogen lamps, xenon lamps, LED lamps, fluorescent lamps, sunlight, electron beam irradiation devices, etc. can be listed. These light sources can be used alone or in combination of two or more.
[0119] These light sources are appropriately selected according to the absorption wavelength of the above-mentioned photocationic polymerization initiator.
[0120] Examples of the light irradiation method for the sealant for an organic EL display element of the present invention include simultaneous irradiation with various light sources, sequential irradiation with a time lag, and a combination of simultaneous irradiation and sequential irradiation. Any of these irradiation methods may be used.
[0121] The cured product obtained by the step of curing the organic EL display element sealant by heating and / or light irradiation may be further coated with an inorganic material film.
[0122] As the inorganic material constituting the inorganic material film, conventionally known materials can be used, for example, silicon nitride (SiN x ), silicon oxide (SiO x ) etc. The inorganic material film may be a single layer or a laminate of various types of layers. In addition, the inorganic material film and the resin film composed of the organic EL display element sealant of the present invention may be alternately repeated to coat the laminate.
[0123] The method for producing the organic EL display element may include a step of bonding a substrate coated with the sealing agent for an organic EL display element of the present invention (hereinafter also referred to as “one substrate”) to another substrate.
[0124] The substrate to which the sealing agent for an organic EL display element of the present invention is applied (hereinafter also referred to as "a substrate") may be a substrate having a laminate having an organic light-emitting material layer formed thereon or may be a substrate not having such a laminate formed thereon.
[0125] In the case where the one substrate is not a substrate for forming the laminate, when the other substrate is bonded, the sealant for the organic EL display element of the present invention may be applied to the one substrate to protect the laminate from the influence of the outside air. That is, when the other substrate is bonded, the sealant may be applied to the entire area where the laminate is to be formed, or when the other substrate is bonded, a sealant portion of a closed mode may be formed in a shape that completely accommodates the area where the laminate is to be formed.
[0126] In addition, as a method for sealing the above-mentioned organic EL display element, a so-called dump-fill sealing method can also be used. That is, first, a curable paste is applied to the substrate of the organic EL display element in a manner that surrounds the periphery of the display portion. Next, the sealant for the organic EL display element of the present invention is applied to the inner side of the applied curable paste, and while preventing the sealant from flowing out due to the curable paste at the periphery, the relative sealing substrates are bonded. Then, a method of curing the curable paste at the periphery and the organic EL display element sealant of the present invention that diffuses inward by heating and / or light irradiation can also be used.
[0127] The step of curing the organic EL display element sealant by heating and / or light irradiation may be performed before or after the step of bonding the one substrate and the other substrate together.
[0128] In the case where a step of curing the sealant for the organic EL display element by heating and / or light irradiation is performed before the step of laminating the one substrate and the other substrate, the usable time of the sealant for the organic EL display element of the present invention from heating and / or light irradiation until the curing reaction is performed and the sealant cannot be bonded is preferably 1 minute or more. When the usable time is 1 minute or more, the one substrate and the other substrate are not over-cured before laminating, and a higher bonding strength can be obtained.
[0129] In the step of bonding the one substrate and the other substrate together, the method of bonding the one substrate and the other substrate together is not particularly limited, but bonding the one substrate and the other substrate together is preferably performed in a reduced pressure atmosphere.
[0130] The preferred lower limit of the vacuum degree under the reduced pressure atmosphere is 0.01 kPa, and the preferred upper limit is 10 kPa. When the vacuum degree under the reduced pressure atmosphere is within this range, it does not take a long time to reach a vacuum state according to the airtightness of the vacuum device or the performance of the vacuum pump, and bubbles in the sealant for the organic EL display element of the present invention when the one substrate and the other substrate are bonded together can be removed more effectively.
[0131] Effects of the Invention
[0132] According to the present invention, it is possible to provide a sealing agent for an organic EL display element which has excellent low degassing properties and coating properties and can obtain an organic EL display element excellent in light extraction efficiency. DETAILED DESCRIPTION
[0133] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0134] (Examples 1 to 8, Comparative Examples 1 to 4)
[0135] The respective materials were stirred and mixed at a stirring speed of 2000 rpm using a stirring mixer according to the mixing ratios shown in Tables 1 and 2 to prepare sealing agents for organic EL display elements of Examples 1 to 8 and Comparative Examples 1 to 4. AR-250 (manufactured by Thinky) was used as the stirring mixer.
[0136] <Evaluation>
[0137] The following evaluations were performed on the sealing agents for organic EL display elements obtained in Examples and Comparative Examples.
[0138] (1) Viscosity
[0139] The viscosity of each of the sealing agents for organic EL display elements obtained in Examples and Comparative Examples was measured using an E-type viscometer at 25° C. and 2.5 rpm. As the E-type viscometer, VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) was used.
[0140] (2) Coating properties
[0141] 0.3 parts by weight of polymer beads having an average particle size of 10 μm were added to 100 parts by weight of each sealant for organic EL display elements obtained in the examples and comparative examples, and the beads were uniformly dispersed by a planetary stirring device. Micropearl SP (manufactured by Sekisui Chemical Co., Ltd.) was used as the polymer beads. Two glass substrates having a length of 5 cm and a width of 5 cm were prepared, 0.1 mL of the obtained dispersion was placed in the center of one of the glass substrates, and the diameter expanded after 30 seconds was measured.
[0142] When the diameter is 5.5 mm or more, the coating property is evaluated as "◎", when the diameter is 5.0 mm or more and less than 5.5 mm, the coating property is evaluated as "○", when the diameter is 4.5 mm or more and less than 5.0 mm, the coating property is evaluated as "△", and when the diameter is less than 4.5 mm, the coating property is evaluated as "×".
[0143] (3) Curing
[0144] The reaction rate when curing each of the sealing agents for organic EL display elements obtained in Examples and Comparative Examples was determined.
[0145] The heat of reaction of the sealing agents for organic EL display elements obtained in Examples 1 to 4, 6, 8 and Comparative Examples 1 to 4 was measured using a differential scanning calorimeter (DSC6220 manufactured by Hitachi High-Tech Corporation), and the reaction rate was calculated using the following formula (I). In the calculation formula (I), H 0 is the heat of reaction when the temperature is raised from 40°C to 200°C at a rate of 10°C / min in an uncured state using an aluminum sample pan in a nitrogen atmosphere. In addition, in the calculation formula (I), H 1 This is the reaction heat generated when the temperature of the organic EL display element sealant that has been heat-cured at 100° C. for 30 minutes is increased from 40° C. to 200° C. at a heating rate of 10° C. / min.
[0146] (H 0 -H1 ) / H 0 (I)
[0147] In addition, the heat of reaction when irradiated with active energy rays and when heated was measured using Photo-DSC (a combination of "DSC Q100" and light source device "Qseries PCA" manufactured by TA Instruments), and the reaction rate was calculated using the following formula (II). In the calculation formula (II), H 2 Yes: Use a high pressure mercury lamp (without cut-off filter) at 3.7 W / cm2 in a nitrogen atmosphere at 25°C. 2 The cumulative amount of illumination is 1.5 J / cm 2 The total heat generated from before the irradiation of the active energy ray to the end of the temperature increase when the temperature is increased from 40°C to 200°C at a rate of 10°C / min immediately after irradiation. The above cumulative light intensity is the cumulative light intensity at a wavelength of 351nm measured using UV-351 (manufactured by ORC). In addition, in the calculation formula (II), H 3 The calorific value (H) of the temperature from cooling to 25°C to heating to 200°C when the temperature is immediately raised to 100°C at a rate of 20°C / min after irradiation with active energy rays under the above conditions, kept at 100°C for 30 minutes, cooled to 25°C at a rate of 10°C / min, and then raised to 200°C at a rate of 10°C / min is 3 ).
[0148] (H 2 -H 3 ) / H 2 (Ⅱ)
[0149] When the reaction rate is 90% or more, the curability is evaluated as "◎", when the reaction rate is 80% or more and less than 90%, the curability is evaluated as "○", when the reaction rate is 60% or more and less than 80%, the curability is evaluated as "△", and when the reaction rate is less than 60%, the curability is evaluated as "×".
[0150] (4) Refractive index and light extraction efficiency
[0151] A 1 mm thick silicone rubber sheet was hollowed out into a rectangle of 20 mm long and 10 mm wide to prepare a mold. The mold was placed on a PET release film, and the sealants for each organic EL display element obtained in the examples and comparative examples were filled into the mold, and then covered with another PET release film in a manner that no bubbles remained, thereby obtaining a laminate. The obtained laminate was sandwiched between two glass plates and fixed to cure the sealant. The sealants for organic EL display elements obtained in Examples 1 to 4, 6, 8 and Comparative Examples 1 to 4 were cured by heating at 100°C for 30 minutes, and the sealants for organic EL display elements obtained in Examples 5 and 7 were cured by using UV-LED at 1500 mJ / cm 2 Irradiate ultraviolet light with a wavelength of 365nm, and then heat at 90°C for 30 minutes to cure. Then, peel off the PET film, and take out the cured product of the sealant from the silicone rubber sheet to obtain a test piece with a length of 10mm, a width of 20mm, and a thickness of 1mm. For the obtained test piece, use an Abbe refractometer to measure the refractive index of the sodium D line at 25°C. As the Abbe refractometer, NAR-4T (manufactured by Atago) was used.
[0152] In addition, considering the difference in refractive index with the electrode or passivation film, when the refractive index is greater than 1.56, the light extraction efficiency is evaluated as "○", when the refractive index is greater than 1.54 and less than 1.56, the light extraction efficiency is evaluated as "△", and when the refractive index is less than 1.54, the light extraction efficiency is evaluated as "×".
[0153] (5) Low degassing
[0154] 300 mg of each sealant for an organic EL display element obtained in the examples and comparative examples were weighed and sealed in a vial to cure. The sealants for an organic EL display element obtained in Examples 1 to 4, 6, 8 and Comparative Examples 1 to 4 were cured by heating at 100°C for 30 minutes. The sealants for an organic EL display element obtained in Examples 5 and 7 were cured by using a UV-LED at 1500 mJ / cm 2 The vial was irradiated with ultraviolet light of a wavelength of 365 nm and then heated at 90° C. for 30 minutes to cure. In addition, the vial was heated in a constant temperature oven at 85° C. for 100 hours, and the amount of vaporized components in the vial was measured using a gas chromatograph-mass spectrometer. As a gas chromatograph-mass spectrometer, JMS-Q1050 (manufactured by JEOL Ltd.) was used.
[0155] When the amount of the vaporized component is less than 50 ppm, the low degassing property is evaluated as "○", when the amount of the vaporized component is greater than 50 ppm and less than 100 ppm, the low degassing property is evaluated as "△", and when the amount of the vaporized component is greater than 100 ppm, the low degassing property is evaluated as "×".
[0156] [Table 1]
[0157]
[0158] [Table 2]
[0159] Industrial Applicability
[0160] According to the present invention, it is possible to provide a sealing agent for an organic EL display element which has excellent low degassing properties and coating properties and can obtain an organic EL display element excellent in light extraction efficiency.
Claims
1. A sealing agent for an organic EL display element, comprising a cationically polymerizable compound and a cationic polymerization initiator, characterized in that: The cationic polymerizable compound includes a cycloolefin oxide type alicyclic epoxy compound and a compound having a biphenyl skeleton and an epoxy group or an oxetane group, In 100 parts by weight of the cationic polymerizable compound, the content of the cycloolefin oxide type alicyclic epoxy compound is 3 parts by weight or more and 45 parts by weight or less, and the content of the compound having a biphenyl skeleton and an epoxy group or an oxetane group is 30 parts by weight or more and 97 parts by weight or less, The content of the compound having a biphenyl skeleton and an epoxy group or an oxetane group is 1.4 parts by weight or more and 20 parts by weight or less relative to 1 part by weight of the cycloolefin oxide-type alicyclic epoxy compound, The sealing agent for an organic EL display element contains no solvent or contains a solvent content of 0.05 wt % or less, and has a viscosity of 10 mPa·s or more and 1000 mPa·s or less measured at 25° C. and 2.5 rpm.
2. The sealing agent for an organic EL display element according to claim 1, wherein The cationically polymerizable compound includes other cationically polymerizable compounds in addition to the cycloolefin oxide-type alicyclic epoxy compound and the compound having a biphenyl skeleton and an epoxy group or an oxetane group.
3. The sealing agent for an organic EL display element according to claim 2, wherein The other cationically polymerizable compound includes at least one selected from 3-ethyl-3-(((3-ethyloxetan-3-yl)methoxy)methyl)oxetane, 1,2:7,8-diepoxyoctane, and 1,2:5,6-diepoxycyclooctane.
4. The sealing agent for an organic EL display element according to claim 3, wherein The other cationically polymerizable compound includes 3-ethyl-3-(((3-ethyloxetan-3-yl)methoxy)methyl)oxetane.
5. The sealing agent for an organic EL display element according to claim 2, 3 or 4, wherein The content of the other cationically polymerizable compound is 10 parts by weight or more and 50 parts by weight or less in 100 parts by weight of the cationically polymerizable compound.
6. The sealant for an organic EL display element according to claim 1, 2, 3 or 4, wherein The cationic polymerization initiator includes a quaternary ammonium salt whose counter anion is a borate system.
Citation Information
Patent Citations
Organic electroluminescent display device and method of manufacturing same
JP2007115692A
Epoxy resin composition and resin-sealed device
JP2009051980A
Resin composition, and cured product (1) thereof
CN104813741A
Sealing composition
CN105557068A
Curable composition, method for producing cured product, and cured product of same
CN109312055A